Medicine as a Performing Art: What We Can Learn About Empathic Communication From Theater Arts. (March 2015) - Eisenberg, Amy; Rosenthal, Susan; Schlussel, Yvette R.
Abstract : The authors describe how they came to the realization that theater arts techniques can be useful and effective tools for teaching interpersonal communication skills (ICS) in medical education. After recognizing the outstanding interpersonal skills demonstrated by two actors-turned-doctors, in 2010 the authors began to develop a technique called Facilitated Simulation Education and Evaluation (FSEE) to teach ICS. In FSEE, actors and residents are coached in empathic, and therefore effective, ICS using a novel technique based on lessons learned from theater arts education. Competence in ICS includes the ability to listen actively, observe acutely, and communicate clearly and compassionately, with the ultimate goal of improving medical outcomes. Resident, actor, and faculty perceptions after two years of experience with FSEE have been positive. After describing the FSEE approach, the authors suggest next steps for studying and expanding the role of theater arts in ICS training.